FAKTOR PRODUKSI USAHA PERKEBUNAN SAWIT DI KOTA BANGUN, KUTAI KARTANEGARA - Sinaga, Ovigeria Subroto; Jumiatun, Jumiatun (Jurnal Magrobis, 2017)
Oil palm plantation products have significance influence for the economy of indonesia. Indonesia is the second largest producer of oil palm products in the world.Oil palm production can not be separated from many production factors. The production factors taken by author are devided into two kind which are capital and labor. The author wants to see the influence of production factors on the oil palm production belonged to H. Usra in Kota Bangun. The author also wants to determine the production function that occurs on the plantation.From the results of statistical calculations using SPSS software in determining the production function of oil palm production is known that the production function that occurs at the beginning of oil palm production is increasing return to scale. It is concluded from the sum of regression coefficient value of production function.From the production function obtained through by calculation of SPSS is known that the two independent variables of capital and labor partially have significant effect on the oil palm production. Simultaneously these two variables also have a significant effect on production.From the production function, the author can know that in the early 9 years of oil palm production activities is labor intensive. This is indicated by the value of the regression coefficient as well as the value of the production elasticity of labor is positive and it has greater value than the regression coefficient of capital.Keywords : Production function, Multiple regression, Return to scale, Capital and labor intensive.